Philosophical Foundation of Chemical Castration for Offenders of Sexual Violence Against Children - Henny Yuningsih; I Nyoman Nurjaya; Prija Djatmika; Masruchin Ruba’I (Sriwijaya Law Review, 2020)
The rate of sexual violence against children in Indonesia is very alarming. Perpetrators of sexual violence against children are usually adults close to the victim, including family members and neighbors. Sexual violence is a violation of human rights. Sexual violence deprives the victim of security and protection, the right to prosper physically and spiritually, the right to be free from torture or treatment that demean human dignity, and the right to live. Chemical castration stipulated in Law No. 17 of 2016 is a form of punishment that is not under criminal law policy in Indonesia, which is based on Pancasila and the 1945 Constitution. Chemical castration formulated in Article 81 Paragraph (7) is not following the values of Pancasila, especially the first principle, namely belief in One and Only God, and the second principle, just and civilized humanity. Substantially, the castration penalty causes an individual to lose the right to continue the lineage and fulfill basic needs as guaranteed in Article 28B paragraph (1) of the 1945 Constitution. The same thing is stated in Article 10, paragraph (1) of Law No. 39 of 1999 concerning Human Rights.